A Pragmatic Analysis Of Phatic Expression On MIG33 Internet Chatting Application - SYAMSUDIN, MUHAMAD NUR (2012)
The study aims to identify the forms of phatic expression on mig33 internet chatting application and to describe the contextual meaning of phatic expression on mig33 internet chatting application. Phatic means the language does not have specific function or purpose. The type of this research is descriptive qualitative research. The writer employs observation and documentation method in collecting the data. After finding the data, the writer signs and makes checklist on phatic expression to look for the words and sentence showing phatic expression. Then, the writer clarifies them based on the characteristic of phenomena, he identifies the form of phatic based on theory of linguistic form, continues the process of spelling based on theory of English abbreviation and phonetic. The results of the research show that first, the forms of phatic expression on mig33 internet chatting application consist of seven kinds. Acronym has 3 data (9,67%), clipping has 16 data (51,61%), invention has 1 data (3,23%), blending has 1 data (3,23%), declarative has 4 data (12,90%), interrogative has 5 data (16,13%), and imperative has 1 data (3,23%). Second, there are ten kinds of meaning in phatic expression on mig33 internet chatting application, namely: those which mean question, 75 data (60,98%), those which mean parting, 2 data (1,63%), those which mean greeting, 7 data (5,70%), those which mean agreement, 9 data (7,31%), those which mean apologize, 5 data (4,06%), those which mean expectation, 6 data (4,87%), those which mean thankful, 2 data (1,63%), those which mean reason, 4 data (3,25%), those which mean conditional, 2 data (1,63%) and those which mean request, 11 data (8,94%).